A study into the problems of cost control for construction projects - Tan, Chin Keng; Adzman, Nur Adilah (2015)
Cost control in the construction industry is to ensure that construction projects are completed within the budget of clients. From the perspective of contractors, understanding and awareness on the practices of cost control are important for them to control their cost for construction projects. In relation to cost control for construction projects, this study aims to identify problems in the practices of cost control and to suggest the strategies to overcome the problems. The method of questionnaire survey was applied to collect data for this study. Questionnaires were distributed to 115 CIDB-registered G7 contractors. The study concludes that changes of design, shortage of labours, inaccurate of quantity-take off, lack of cost information, lack of expertise, lack of knowledge and inaccurate of cost estimate are the main problems in cost control practices. The study proposes that providing cost control training to the staff, managing the inflation risk by allowing fluctuation of price in the contract, minimizing the changes in design and constantly update the cost data are the strategies to overcome problems in cost control practices for construction projects.